Utricularia uliginosa Vahl (Lentibulariaceae): A New Distributional Record for Andaman and Nicobar Islands, India - Kamble, M. Y.; Sardesai, M. M.; Karthigeyan, K.; Chandore, A. N.; Gosavi, K. V. C. (Indian Forester, 2019)
No Abstract.